Clinical outcome of locking plate fixation in distal tibia fractures - Ahmad Shakib Mohebi ,; Rana Dilawaiz Nadeem,; Ranjit Kumar Sah,; Iftikhar Mohy-Ud-Din,; Muhammad Akhtar, (Journal of the Pakistan Medical Association, 2023)
Objective: The objectives of this study were to assess the outcome of close distal tibial fractures fixed with pre-contoured locking plate using MIPPO technique in terms of union and infection. Methods: This study was conducted in the Department of Orthopaedic Surgery and Traumatology from Sep 2013 to May 2017. We enrolled 40 cases with close distal tibial fractures. Fractures were managed with locking compression plate using MIPPO technique. Patients were followed for 12 months post-fracture stabilization. Results: In this study total 40 patients (24 males and 16 females) were included. Male to female ratio of the patients was 1.5:1. The mean age of the patients was 44.70±13.67 years with minimum and maximum ages of 18 & 60 years respectively. All fractures united with the mean union time of 16±4 weeks. The infection rate was 5%.